Gene expression profiling of lichenoid dermatitis immune‐related adverse event from immune checkpoint inhibitors reveals increased CD14+ and CD16+ monocytes driving an innate immune response. (11th April 2019) - Curry, Jonathan L.; Reuben, Alexandre; Szczepaniak‐Sloane, Robert; Ning, Jing; Milton, Denái R.; Lee, Chi H.; Hudgens, Courtney; George, Saira; Torres‐Cabala, Carlos; Johnson, Daniel; Subramanya, Sandesh; Wargo, Jennifer A.; et al.
Abstract : Background: Cancer patients receiving antibodies abrogating immune checkpoint pathways may develop a diverse array of immune‐related adverse events (irAEs), of which lichenoid dermatitis (LD) is the most common. The mechanism driving the emergence of these irAEs remain understudied, underscoring a critical need to determine the unique gene expression profiles and immune composition in LD—irAE. Methods: LD—irAE (n = 3) and benign lichenoid keratosis (BLK) control (n = 3) were profiled with NanoString nCounter PanCancer Immune Profiling Panel interrogating the mRNA levels of 770 genes. Immunohistochemical (IHC) studies (n = 14 samples) for CD14, CD16, T‐Bet, Gata‐3, and FoxP3 were further evaluated using Aperio digital image analysis. Results: The LD—irAE showed downregulation of 93 mRNA transcripts ( P < 0.05) and upregulation of 74 mRNA transcripts ( P < 0.04) including toll‐like receptor (TLR) 2 and TLR4 ( P < 0.05). CD14 + and CD16 + monocytes quantified by IHC (H‐score) were higher in LD—irAE than in the BLK control ( P < 0.05). The immune composition of LD—irAE exhibited higher numbers of T‐Bet + (Th1) cells compared with Gata‐3 + (Th2) cells ( P = 0.016) and lower numbers of FoxP3 (T regulatory) cells ( P = 0.008). Conclusions: LD—irAE exhibited activation of CD14/TLR innate immune response with increased CD14 + and CD16 + monocytes compared with BLK control. CD14/TLR signaling may drive the development of LD—irAE.